Inferior alveolar nerve anaesthesia: A rare complication of orthodontic tooth movement. (December 2019) - Mahmood, Hanya; Stern, Melanie; Atkins, Simon
Inferior alveolar nerve (IAN) damage is a rare but recognised complication of dental procedures including third molar surgery, implant surgery, endodontic treatment and local anaesthetic injections. However, it is rarely caused by orthodontic tooth movement. This report highlights a case of temporary IAN anaesthesia to the right mental region, which was likely to have occurred secondary to the orthodontic uprighting of a lingually tilted molar using a high strength arch wire. Immediate deactivation of the appliance and an acute reducing dose of systemic steroids resulted in complete resolution of symptoms. To the best of the author's knowledge, there have been seven previously described cases of IAN paraesthesia but no cases reporting IAN anaesthesia secondary to orthodontic fixed-appliance treatment. This case highlights the importance of dentists practising orthodontics to have an awareness of the clinical and radiographic signs that may indicate a high-risk case requiring appropriate referral for cone beam imaging and careful orthodontic planning. Furthermore, this case emphasises the need to warn high-risk patients of the symptoms of this rare complication and how it may be managed. This will ultimately help to minimise the risk of litigation and optimise patient experience and care.